Land characteristics and management for the development of Geragai Agro Techno Park Jambi Province. Issue 1 (February 2021) - Hendri, J; Purnamayani, R
Abstract: Geragai Agro Techno Park (ATP), Jambi Province is a pilot area to accelerate agricultural technology transfer. The ATP pilot area is built in a swampland agro-ecosystem which requires optimal land management. The purposes of this study were to identified soil chemical properties at ATP, to build partitioned canals based on hydro-topography and land characteristics, and to contribute to land management at ATP. This study was carried out using a direct survey by observing field conditions, taking and analysing soil samples, interviewing farmers, and conducting a literature study in January - December 2016. Based on the results, the soil fertility rate at ATP was in the low to the moderate category with 80 to 120 cm pyrite layer depth. Based on soil survey, hydro-topographic survey, and land characteristics, it is recommended to build partitioned canals on these lands to prevent pyrite oxidation and maintain water availability during the rainy and dry seasons. With the partitioned canal, Geragai Agro Techno Park can increase the cropping index to 300 with the rice-secondary crop-secondary crop pattern adjusted to farmer preferences.